Fertility control for managing free-roaming feral cattle in Hong Kong. Issue 48 (19th November 2018) - Massei, Giovanna; Koon, Ka-Kei; Law, Siu-Iun; Gomm, Matt; Mora, Darcy S.O.; Callaby, Rebecca; Palphramand, Kate; Eckery, Douglas C.
Abstract: Human-wildlife conflicts are increasing worldwide. For instance, growing numbers of free-roaming feral cattle in Hong Kong are causing traffic accidents and damaging crops. Public antipathy towards lethal methods to manage wildlife has promoted research into alternative options, such as fertility control. The aims of this study were to assess the potential side effects and effectiveness of the injectable immunocontraceptive vaccine GonaCon on free-roaming feral cattle in Hong Kong. Sixty female cattle were captured and randomly assigned to treatment or control groups. Treatment animals were administered one dose of GonaCon, followed by a booster dose 3–6 months later. Control animals were administered an equivalent dose of a saline solution. The side effects of GonaCon were assessed by monitoring injection site, body condition and body weight at vaccination, at the booster stage and one year after initial vaccination. At the same times, blood samples were collected to quantify antibodies to the vaccine and to assess pregnancy status. GonaCon did not affect the body weight or body condition of cattle and had no adverse side effects such as injection site reactions, limping or abnormal behaviour. GonaCon did not appear to interrupt ongoing pregnancies but reduced fertility significantly: the proportion of pregnant animals in the GonaCon-treated group decreased from 76% at initial vaccination to 6% one year after vaccination, compared to 67% and 57% respectively in the control group. There was no difference between antibody titres at the booster stage or one year post vaccination, suggesting the booster dose maintained antibody levels. This study confirmed that GonaCon is safe and effective in inducing infertility in feral cattle, with a booster dose critical for maintaining infertility.